Reinterpreting Snow White: Adaptation, audience response, and commercial reception - Dian Nur Endah; Muhammad Arkan Dafi; Fatima Kamila (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study examines Disney’s Snow White as a contested adaptation by investigating the relationship between narrative reinterpretation, audience reception, and cultural industry dynamics. With live-action remakes dominating global media, understanding their failures is now a critical focus for media and cultural scholars. Drawing on adaptation, fairy tale, and cultural industry theories, this study examines how the film reconfigures Snow White and how contemporary audiences receive these changes. Methodologically, the research employs qualitative comparative analysis of the two films alongside interpretive analysis of audience responses drawn from IMDb, Rotten Tomatoes, and Metacritic. The findings indicate that the 2025 adaptation shifts the fairy tale’s core logic from romantic salvation and moral simplicity toward political agency, justice, and leadership. While this reinterpretation aligns with contemporary values, it destabilizes the symbolic coherence and grammar that give the fairy tale its traditional meaning. Audience responses reveal widespread resistance to this transformation, expressed through criticism of casting, characterization, visual aesthetics, narrative logic, and emotional depth. The study contributes to adaptation and media scholarship by showing that adaptation failure is often structural rather than incidental. Such failure emerges when narrative strategy, cultural memory, and market positioning become misaligned.